Staged reservation scheme for optical burst switching networks - Abid, A.; Abbou, F. M.; Ewe, Hong Tat (The Institute of Electronics, Information and Communication Engineers, 2005)
In this paper, the Staged Reservation Scheme (SRS) is introduced for Optical Burst-Switched (OBS) networks based on Just-Enough-Time ( JET) protocol. With SRS the Data-Bursts are segmented into equal sub-bursts ( data segments). SRS is to address the feasibility issues ( e. g. segments delineation, and trailer-messages creation) associated with the implementation of burst segmentation techniques. The burst control packet is modified to carry the segments' number and length, therefore the data-bursts length. Furthermore, the network resource reservation is performed in stages to resolve contentions at the control packets level, and to reduce the packets loss probability.